Role of smoking in functional dyspepsia and irritable bowel syndrome: three random population‐based studies. Issue 1 (13th May 2021) - Talley, Nicholas J.; Powell, Nicholas; Walker, Marjorie M.; Jones, Mike P.; Ronkainen, Jukka; Forsberg, Anna; Kjellström, Lars; Hellström, Per M.; Aro, Pertti; Wallner, Bengt; Agréus, Lars; Andreasson, Anna
Summary: Background: It is uncertain if functional dyspepsia (FD) or irritable bowel syndrome (IBS) are linked to smoking, and smoking cessation is not part of the routine advice provided to these patients. Aim: To assess if smoking is an independent risk factor for FD and IBS. Methods: Three population‐based endoscopy studies in Sweden with 2560 community individuals in total (mean age 51.5 years, 46% male). IBS (14.9%), FD (33.5%), and associated symptoms were assessed using the validated abdominal symptom questionnaire, and smoking (17.9%) was obtained from standardised questions during a clinic visit. The effect of smoking on symptom status was analysed in an individual person data meta‐analysis using mixed effect logistic regression, adjusted for snuffing, age and sex. Results: Individuals smoking cigarettes reported significantly higher odds of postprandial distress syndrome (FD‐PDS) (OR 10‐19 cig/day = 1.42, 95% CI 1.04‐1.98 P  = 0.027, OR ≥20 cig/day = 2.16, 95% CI 1.38‐3.38, P  = 0.001) but not epigastric pain. Individuals smoking 20 or more cigarettes per day reported significantly higher odds of IBS‐diarrhoea (OR = 2.40, 95% CI 1.12‐5.16, P  = 0.025), diarrhoea (OR = 2.01, 95%CI 1.28‐3.16, P  = 0.003), urgency (OR = 2.21, 95%CI 1.41‐3.47, P  = 0.001) and flatus (OR = 1.77, 95%CI 1.14‐2.76, P  = 0.012) than non‐smokers. Smoking was not associated with IBS‐constipation or IBS‐mixed. Conclusion: Smoking is an important environmental risk factor for postprandial distress syndrome, the most common FD subgroup, with over a twofold increased odds of PDS in heavy smokers. The role of smoking in IBS‐diarrhoea, but not constipation, is also likely important. Abstract : Smoking cessation is not currently part of the routine advice provided to individuals with functional dyspepsia (FD) and irritable bowel syndrome (IBS). Individuals smoking cigarettes reported significantly higher odds of postprandial distress syndrome (FD‐PDS): OR 10‐19 cig/day = 1.42 OR ≥20 cig/day = 2.16. Individuals smoking 20 or more cigarettes per day reported significantly higher odds of IBS‐diarrhea: OR = 2.40.Created with Biorender.com